A theoretical model on the influence of ring joint stiffness on dynamic responses from underground tunnels. (30th October 2019) - He, Chao; Zhou, Shunhua; Guo, Peijun; Di, Honggui; Zhang, Xiaohui
Highlights: An accurate and efficient model is presented to predict the dynamic responses from underground tunnels. The effect of the tunnel ring joint stiffness on the ground vibrations is investigated. The effect of the tunnel ring joint stiffness on the dynamic responses of foundation soil is investigated. The effect of the tunnel ring joint on soil vibrations under different thicknesses of tunnel ring is investigated. Abstract: The vast majority of underground tunnels are constructed by the shield-driven method, resulting in the tunnel structure being periodically jointed in the longitudinal direction. Significant studies have been proposed to predict vibrations from a homogeneous tunnel, while less attention has been paid to the effect of the tunnel ring joint and its stiffness property. This paper develops a new three-dimensional analytical model to investigate the influence of the ring joint stiffness on the dynamic responses from underground tunnels. The solution for a harmonic moving load applied to the periodic jointed tunnel is derived by using the periodic-infinite structure theory. The solution for wave propagation in the saturated porous medium is developed by the Biot's theory and potential decomposition. By using the wave transformation, the periodic jointed tunnel is coupled with the saturated soil via the boundary conditions on the tunnel-soil interface. This model is validated via the comparison with existing solutions. Numerical results for a moving harmonic load applied to the periodic jointed and homogeneous tunnels are analysed in detail. It is found that the tunnel ring joint stiffness has a significant effect on the soil vibration levels, indicating that the tunnel ring joint and its stiffness property should be considered in the prediction of ground vibrations induced underground railways.